Resorufin based fluorescence 'turn-on' chemodosimeter probe for nitroxyl (HNO). Issue 103 (6th October 2015) - Bobba, Kondapa Naidu; Zhou, Ying; Guo, Lin E.; Zang, Tie Nan; Zhang, Jun Feng; Bhuniya, Sankarprasad
Abstract : A cellular responsive, highly selective fluorogenic and chromogenic chemodosimeter probe for HNO is developed. Abstract : A cellular responsive, highly selective fluorogenic and chromogenic chemodosimeter probe for HNO is developed. This new probe showed ∼30 fold fluorescence enhancement in the presence of HNO and is sensitive to HNO at concentrations as low as 0.02 μM. Further, it is capable of detecting HNO levels in cellular milieus as well as in live specimens e.g. C. elegans .